Penilaian Kesesuaian Lahan Tanaman Perkebunan Berbasis Sistem Informasi Geografis (SIG)di Kecamatan Ciomas Kabupaten Serang - Nuniek Hermita; Putra Utama; Andi Apriany fatmawaty; Esta Silviyani; Andree Syailendra (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
This study aims to determine land suitability class for of plantation crops, namely; cocoa, arabica coffee and durian in Cemplang region, Ciomas district, Serang Regency. The research used several stages of research method including; collecting data and information, determining soil sample points and field surveys, taking soil samples and field observation, conducting laboratory analysis and assessing land suitability classes. Data processing was carried out using GIS through the ArcGIS application by overlaying and applying the matching method of land suitability parameters. The results showed that the assessment of land suitability at two sample points for cocoa plants was quite suitable (S2) with limiting factors for nutrient retention and erosion hazard, arabica coffee plants were not suitable (N) with temperature limiting factors, while the durian plants were by the marginal (S3) with the limiting factor of water availability. Efforts to improve the land can be made by making terracing, making drainage, applying agroforestry patterns, adding organic matter, liming and fertilizing.Keywords: land suitability, plantation crops, SIG